Comparing antithyroid drugs vs. radioactive iodine in paediatric Graves’ disease: literature review - Akshat Sinha; Reuben Oza; Brandon Karamveer Sangha; Arshia Akhavan-Mofrad; Arvin Suddhi (Thyroid Research)
Abstract Introduction Paediatric Graves’ disease (PGD) is an autoimmune condition, which if left untreated, can result in cardiac complications. National Institute for Health and Care Excellence (NICE) Guidance (NG145) advocates the use of antithyroid drugs (ATD) as first-line therapy for PGD, with a consultation to consider a move to definitive therapy in the form of radioactive iodine (RAI) or thyroidectomy if the initial 2-year course failed to achieve normal thyroid function. We aim to evaluate the effectiveness, adverse events, and potential predictors of remission for ATD and RAI in treating PGD. Methods A thorough guideline search of NICE Evidence and Royal College of Physicians (RCP) guidelines and policy was conducted to yield a guideline relevant to our review question. A literature search of the Cochrane Library, MEDLINE, EMBASE and PubMed, alongside a clear inclusion and exclusion criteria was utilised to generate systematic reviews and primary literature exploring the efficacy and adverse effects (AEs) of ATD and RAI. Our guideline, systematic reviews and primary literature were appraised using AGREE-II, AMSTAR 2 and CASP respectively. Results The search strategy yielded one NICE guideline (NG145) published in November 2019, two systematic reviews published after November 2019 and four primary studies, published after the most recent systematic review (August 2020). All studies concluded that ATD and RAI are effective treatment options for PGD. With regards to AEs, RAI and ATD were safe treatment options, with the latter having the least severity of complications. Conclusions In patients who have been identified to have predictors of remission, we agree with NG145 and ATD should be offered as first-line treatment. However, for those who do not have characteristics aligning with the predictors of remission, RAI should be offered as first-line therapy. Future studies should investigate the effect of biochemical parameters to identify predictors of remission, to aid the choice of treatment in paediatric Graves’ disease treatment.